Diamagnetism of layered organic conductors - Kirichenko, O.V.; Peschansky, V.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Temperature dependence of the magnetic susceptibility of layered organic conductors with an arbitrary dispersion law, placed in a strong magnetic field, is analyzed. It is shown that quasi-two-dimensional character of the electron energy spectrum of such conductors results in strong dependence of the diamagnetic contribution to the magnetization upon the applied magnetic field orientation. Experimental investigation of the anisotropy of the magnetic susceptibility makes it possible to study separately the diamagnetic and paramagnetic contributions to the magnetization of layered conductors.